Manajemen Madrasah Dalam Meningkatkan Mutu Pendidikan Pada MI Al-Muhajirien Bekasi - Sarnoto, Ahmad Zain (Statement: Jurnal Media Informasi Sosial dan Pendidikan, 2023)
This research reveals about madrasa management which can be interpreted as everything related to the management of the educational process to achieve predetermined goals, both short, medium and long term goals. The aim of this research is to determine the management of Ibtidaiyah madrasas in improving the quality of education, including: (1) Madrasah program planning; (2) Implementation of the Ibtidaiyah madrasah program and (3) Obstacles it faces. This research uses a qualitative approach with descriptive methods, data collection techniques are carried out through interview guidelines, observation guidelines and documentation studies. The research subjects were the head of the Ibtidaiyah madrasa and teachers at MI Al-Muhajirien Bekasi. The results of the research found: (1) Planning for the Madrasah Ibtidaiyah program includes: teaching programs, including: the need for teachers, division of teaching duties, procurement of textbooks, learning tools and teaching aids, procurement or development of madrasah Ibtidaiyah laboratories, procurement or development of libraries Ibtidaiyah madrasah, learning outcomes assessment system, and curricular activities; (2) Implementation of the Ibtidaiyah madrasah program, namely the strategy implemented to achieve an increase in the quality of education, including: program socialization, SWOT analysis, problem solving, quality improvement, and monitoring and evaluation of school program implementation; and (3) Obstacles in planning the Ibtidaiyah madrasah program, including lack of community participation and economic difficulties so that their support for school management is also low. It is hoped that supervisors will be able to direct and supervise the head of the Ibtidaiyah madrasah in improving the quality of education regarding the planning of the Ibtidaiyah madrasah program, implementation of the program and the obstacles they face in an appropriate, effective and efficient manner so that the quality of education in the Ibtidaiyah madrasah can be improved